Strategy on the National Unity and Politics Agency (KESBANGPOL) in Maintaining Ethnicity and Religious Relations Based on Huma Betang Philosophy in Central Kalimantan - Suprayitno Suprayitno; Triyani Triyani; Putri Fransiska Purnama Pratiwi (Budapest International Research and Critics University, 2019)
The population in Central Kalimantan is plural, both in terms of ethnicity and religion. The indigenous people are Dayaks, but other ethnic groups also live side by side and become part of the people of Central Kalimantan such as Banjar, Javanese, Bugis, Madurese, Batak, Chinese, and so on. Those ethnics currently live in Central Kalimantan. Also, the followers of the religion, such as Muslims, Christians, Catholics, Hindus, Buddhists, and Kaharingan are developing rapidly in Central Kalimantan. The plurality of ethnicity relations has the potential for conflict because the differences in tradition and culture become cultural boundaries which become boundaries among the communities. In 2001 ago, Central Kalimantan Province had experienced a dark period of riots under the ethnicity reason in Sampit, Kotawaringin Timur Regency. The National Unity, Politics and Community Protection Agency (Kesbangpol) is an office in Central Kalimantan Province which the main task is the development of the values of nationalism and conflict management. Then, the particular study aims to analyze the strategies of Kesbangpol in maintaining harmony among religious & ethnic groups in Central Kalimantan based on Huma Betang Philosophy.